Production and Operations Symposium 2007
DOI: 10.2118/106707-ms
|View full text |Cite
|
Sign up to set email alerts
|

Critical Conditions for Effective Sand-Sized Solids Transport in Horizontal and High-Angle Wells

Abstract: fax 01-972-952-9435. AbstractEffective removal of small sand-sized solids is critical for successful drilling and completion operations in sand reservoirs. Recent experience in extended reach drilling also indicates that inefficient transport of smaller cuttings is a main factor for excessive drag and torque. This study was undertaken to determine two critical conditions for efficient transport of small solids. The two conditions are represented by the Critical Re-Suspension Velocity (CRV), the minimum fluid v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This outstanding performance has shown that if polypropylene beads were to be commingled with drilling fluid in any drilling operations, it would enhance the cuttings transport and invariably improve the effectiveness of the wellbore cleaning by the transporting fluid. The improvement recorded by the drilling mud with polypropylene beads has been influenced by two major forces that act on slipping cuttings of imperfect sphere in a turbulent flow, namely the gravitational and drag forces (Clark & Bickham 1994;Duan et al 2007;Skalle 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This outstanding performance has shown that if polypropylene beads were to be commingled with drilling fluid in any drilling operations, it would enhance the cuttings transport and invariably improve the effectiveness of the wellbore cleaning by the transporting fluid. The improvement recorded by the drilling mud with polypropylene beads has been influenced by two major forces that act on slipping cuttings of imperfect sphere in a turbulent flow, namely the gravitational and drag forces (Clark & Bickham 1994;Duan et al 2007;Skalle 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, mud rheology [20][21][22][23][24], particle size [20,21,23,25,26], and drillpipe rotation [6,24,27] continued to be studied.…”
Section: The Effects Mud Rheology Particle Size and Drillpipe Rotatimentioning
confidence: 99%
“…In addition, Duan et al [26] still conducted experiments to determine the critical resuspension velocity (CRV) and the Saasen et al [12] Drillpipe rotation Pipe rotation leads to more efficient cuttings transport for gel structure cuttings bed.…”
Section: The Effects Mud Rheology Particle Size and Drillpipe Rotatimentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is very important for horizontal and ERW wells to enhance cuttings transport efficiency. Many researchers have developed a series of helical hole cleaning tools to improve hole cleaning condition and obtained good results [4][5][6]. These tools have helical blades on their surface, and outer diameters of these blades are close to drill pipe sub.…”
Section: Introductionmentioning
confidence: 99%